Female directors: Why are some less informed than others? - Mobbs, Shawn; Tan, Yongxian; Zhang, Shage (2021)
We find the limited supply of female directors, rather than gender differences or boardroom biases, can create an informational disadvantage for some female independent directors, as measured by their open market trading profits. The information disparity is largely isolated to firms with abnormally low representation by female directors. Female independent directors who are located further away from the company’s headquarters, have less industry experience or have shorter tenure exhibit the most limited information access. Accounting for these obstacles reduces the gender disparity in information. We further find that this information disparity among female independent directors contributes to the variation in their influence on board monitoring. More informed female independent directors are associated with fewer restatements, lower abnormal CEO compensation and higher Tobin’s Q. Our results have several policy implications.